MiR- 146b-5p inhibits Candida albicans-induced inflammatory response through targeting HMGB1 in mouse primary peritoneal macrophages - Jing Cheng; Xiaoxing Tian; Chuanxin Wu; Jiaojiao Wang; Huiling Liu; Sha Cheng; Hang Sun (Heliyon)
Background: Candida albicans (C. albicans) is one of the most common pathogens associated with deep fungal infection, which represents a serious threat to human health. Although high mobility group box 1 (HMGB1) plays a key role in C. albicans infection, its mechanism is unclear. We aimed to explore the regulation of small-molecule non-coding RNA (miRNA) for HMGB1 in C. albicans infection. Methods: Mouse primary peritoneal macrophages (MPMs) were isolated successfully. The optimum conditions for C. albicans infection were selected by Western blot and ELISA. The miRNA differential expression profiles of C. albicans infection were screened and verified by 6 miRNA gene chips and qRT-PCR. The direct regulation of the target gene HMGB1 by mmu-miR-146b-5p was confirmed through a dual-luciferase assay. The levels of mmu-miR-146b-5p, HMGB1, inflammatory mediators, p-IKK, IKK, p-IκBα, IκBα and NF-κB p65 were tested by qRT-PCR, Western blot, and ELISA. The nuclear and cytoplasm translocation of HMGB1 and NF-κB p65 were detected by Western blot and laser confocal microscopy. After siHMGB1 transfection, the expression levels of HMGB1, inflammatory mediators, p-IKK, IKK, p-IκBα, IκBα and NF-κB p65 were assessed using Western blot, qRT-PCR and ELISA. Results: In our study, MPMs were successfully extracted and infected with C. albicans at optimum conditions of 1.5 × 107 CFU/mL for 36 h. Through miRNA gene chips analysis, 40 differential genes were screened. mmu-miR-146b-5p could directly and negatively regulate the expression and translocation of HMGB1, inhibit the expression of inflammatory mediators, and might participate in the NF-κB signaling pathway in a HMGB1-dependent manner under C. albicans infection. Conclusion: mmu-miR-146b-5p may play an anti-inflammatory role in treating C. albicans infection and provide a novel target for it.